Evidence Regarding Ethiopia's Import-Export of Mushrooms - Tensaye Abate; Gonche Girma; Shiferaw Alem (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
Ethiopia has favorable agro-climate, topography, relatively low-cost labor, and rich fungal biodiversity. However, the country has a poor response to mushroom production and hence, currently, a huge amount of mushrooms is imported to the country. Information on the import-export trends of the mushrooms trade and market is lacking for taking appropriate measures. The study aims to evaluate the current status and future trends as well as prospects of mushroom import export in Ethiopia. The imported-exported data were collected from Ethiopian Custom Commission in the years of 1997 – 2020. The analysis was conducted using descriptive statistical tools and the ARIMA model in excel and STATA, respectively. The result indicates that the average imported and exported quantity is 88.3 and 5.1 tonnes of mushrooms per year, respectively. Similarly, the country spent an average of US$ 154,199 per year on imported mushrooms while it earned an average of US$ 11,074 per year from exported mushrooms, which is a trade deficit. The result further indicated that on average the quantities of mushrooms imported to the country and the expenditure to import increased yearly by 53 % and 44%, respectively.  The forecasted result shows that Ethiopia will spend 483,528.3 US$ on mushroom imports in 2040 as indicated in the findings. However, mushroom productions pave the way for national revenue if given serious consideration and will reduce the food import value. Further, it is recommended that the country has to emphasize the expansion of mushrooms to meet the growing demand and substitute the imported mushroom.